Optimal hydrocarbon based working fluid selection for a simple supercritical Organic Rankine Cycle. (1st September 2021) - Das, Debranjan; Kazim, Mohammad; Sadr, Reza; Pate, Michael
Highlights: Analysis of Supercritical Organic Rankine Cycle operating on hydrocarbons. Energy and Exergy analysis of the cycle were assessed for a low-grade heat source. Specific Exergy Costing method was used for Exergoeconomic analysis of the system. Working fluid based on various cycle parameter performance was selected for system. Abstract: In this paper, several hydrocarbons' performance as a working fluid for a supercritical Organic Rankine Cycle are studied. Energy, exergy, and exergoeconomic analysis are conducted for the cycle operating with a low-grade waste heat source. Initially, fifteen different working fluids, primarily hydrocarbons, were considered based on their environmental characteristics, global warming potential, ozone depletion potential, flammability, and toxicity. The cycle efficiency for each working fluid was analyzed for different cycle operating pressures and different inlet heat source temperatures from 400 K to 500 K for a constant turbine work output. Three different trends of cycle performance characteristics were observed for various working fluids with the cycle operating at different evaporator pressures and source inlet temperatures. The working fluids that exhibited similar characteristic trends were then categorized into families for further analysis. Three hydrocarbons, i.e., Dimethyl Ether, R1234yf, and Diethyl Ether, were each selected as the representative of their respective family, along with Isobutane as the reference working fluid for comparison. After detailed energy and exergy analyses, Dimethyl Ether and Isobutane were found to be promising working fluids for the range of pressure and source inlet temperatures considered. Finally, the exergoeconomic analysis showed Dimethyl Ether to be the optimal working fluid based on the unit cost of net work produced and the total cost of exergy destruction, which were calculated to be (59.18 ± 0.49) /MWh and (8.92 ± 0.48) /h, respectively, when operating at 450 K.